Review: Güldemann, Tom. 2008. Quotative indexes in African languages: A synchronic and diachronic survey. Berlin: Mouton de Gruyter. (Empirical Approaches to Language Typology 34). ISBN 978-3-11-018590-4 - (:unkn) unknown (My University, 2011)
The book under review provides a thorough construction-oriented synchronic and diachronic investigation of quotative indexes in a representative sample of 39 African languages. The study is typologically and theoretically well-informed and offers a good of deal of thought-provoking findings and insightful generalizations of general interest, well beyond the Africanist readership whose attention the title may attract most. The book also contains a wealth of language-specific data and analyses, both synchronic and diachronic. These data and analyses will be relevant not only to the specialists in the respective languages and language families, who could profit a lot from the new perspective on the data they may already be familiar with, but also to a readership attentive to issues of cross-linguistic diversity and language change.
Keywords: African Research